(untitled) (Research, Society and Development, 2021)
This study aimed to carry out a systematic literature review about olives, extraction methods, physical and chemical characterization and identity and quality parameters of olive oils, as well as technological alternatives for using by-products. Olive oil is the oil extracted from the ripe fruits of the olive tree (Olea europaea L.). Trees have been cultivated in the Mediterranean Region for several centuries and thousands of cultivars differ by weight, size and chemical characteristics of the fruits. Currently, olive oil is produced worldwide and the olive plant was recently introduced in the city of Diamantina, Minas Gerais. The lipid content is mostly composed of oleic acid and smaller fractions of phenolic compounds, phytosterols and pigments, substances with antioxidant and bioactive activities that promote oxidative stability of the oil and beneficial effects on human health. The main extraction of olive oil consists of crushing, pressing and centrifuging, generating by-products that can be reused for recovery of compounds or generation of new products in the food industry. After extraction, the oil is submitted to several physical and chemical analyzes to define the identity and quality parameters, according to international standards. The main characteristics that define the quality of olive oil are free acidity, peroxide index, specific extinction index, instrumental color and fatty acids profile.